110 MULTIPLE COLONIC ULCERS IN AN ADULT CYSTIC FIBROSIS PATIENT ON PANCREATIC ENZYME SUPPLEMENTS. (1st January 2005) - Jain, S.; Blanchard, K.; Minocha, A.
Abstract : Fibrosing colonopathy is a well-described complication of cystic fibrosis (CF) patients on pancreatic enzyme supplements (PES). While ulcerogenic effects have been postulated, endoscopic appearance of ulcers has never been described. We present a patient with CF on PES whose colonoscopy revealed previously undescribed well-circumscribed oval, discrete ulcers highly suggestive of direct ulcerogenic effects of the pancrease capsules. Endoscopic pictures will be presented. The patient is a 29-year-old white male with a history of CF who was seen in the hospital for watery diarrhea and abdominal pain. His medications included tobramycin, ceftazidime, aztreonam, bupropion, MgOH, lansoprazole, pancrease MT-16 (10 capsules/day), albuterol, dornase alfa inhaled, and nasal fluticasone. His abdominal examination was unremarkable. His stool was positive for Clostridium difficile toxin A, for which he was treated with metronidazole. The stool became negative for C. difficile toxin after five days, but he persistently complained of diarrhea and abdominal pain. Stool cultures for Salmonella, Shigella, Campylobacter, Aeromonas, Plesiomonas, Vibrio, Yersinia and E. coli were negative as were the antigens for Giardia and Cryptosporidium parvum. Colonoscopy revealed multiple, well-circumscribed ulcers one cm in diameter scattered throughout the colon. All these ulcers were discrete, of the same size and shape, and were surrounded by normal mucosa. Pathology revealed focal ulceration and acute inflammation at the borders of the ulcers. There was no evidence of pseudomembranes or volcano lesions, characteristic of C. difficile colitis. Acid fast and Grocott methenamine-silver stains were negative for acid-fast bacteria and fungi. Immunostains were negative for CMV and herpes simplex virus. He improved gradually with supportive care and was discharged home. These previously undescribed colonoscopy findings in our CF patient suggest the direct ulcerogenic effects of the capsules. It is possible that the enteric-coated pancrease capsules did not dissolve in the small intestine and adhered to the colonic mucosa resulting in direct injury. While it is not possible to say whether the injury was secondary to the coating or to the enzymes themselves, this provides insight in the pathogenesis of pancreatic enzyme induced colonic injury leading to fibrosis and subsequent stricture formation.